Analysis Of Cultural And Social Influences On The Decision To Purchase Packaged Cooking Oil Mediated By Consumer Psychology (Gelugur Market Case Study) - Megawati Mora Putri; Elfitra Desy Surya; Mesra b (International Journal of Management, Economic and Accounting, 2025)
The purpose of the study is to analyze the cultural and social influence on the decision to purchase packaged cooking oil mediated by consumer psychology. Based on the identification of problems, several critical issues were found, such as the lack of cultural influence, social circumstances such as economic ability to influence purchasing decisions, and advertisements for oilita packaged cooking oil products that did not attract the attention of consumers. This study does not limit the age of buyers who are 20 years old and above. The sample was taken using the snowball sampling method with a total of 120 respondents. The data was analyzed using Structural Equation Modeling (SEM) using the Smart Partial Least Squares (PLS) method. The results of the study show that all variables, namely cultural and social, have a positive and significant influence on consumer purchase decisions and psychology. The hypothesis with the highest value is the influence of consumer psychology on purchase decisions with an original sample (O) value of 0.663 and a T-Statistic of 6.382. On the other hand, the hypothesis with the lowest value is the influence of culture on purchasing decisions with an original sample value (O) of -0.211 and a T-Statistic of 1.769 so that this hypothesis is not accepted. The conclusion of this study emphasizes that as an Indonesian citizen to use domestic products such as oilita packaged cooking oil in the development of daily life needs. The advice for companies that own oilita packaged cooking oil is that the company is expected to be able to provide even better innovation by providing information on the content in oil and its advantages through attractive advertisements such as on television and on social media.